Video Equipment and Video Shot Composition - Ricky Telg; Peyton Beattie (EDIS, 2021)
This 6-page publication about video equipment and video shot composition is part of a series on developing effective video production practices. This series also covers video production, scriptwriting, and video editing. Minor revision by Ricky Telg and Peyton Beattie; published by the UF/IFAS Department of Agricultural Education and Communication.